Attityder till återintroduktion av visent i Sverige - Bergsten, Axel (2012)
The European bison is a species which is no longer present in the wild fauna of Sweden. Reintroduction has been proposed in several different forums. Reintroduction is an attempt to reestablish a viable population of a species in an area to which it is native. To make such an operation successful in the long run it is essential to know the attitudes of the stakeholders involved. This study has sensed the attitudes towards reintroduction of European bison to Sweden. It was done through a survey sent to the Wildlife Management Boards in all the counties of Sweden and to people applying for agricultural subsidies (JS). The results reveal that a majority would support a reintroduction project. The primary arguments for a reintroduction were if it would aid conservation of the species and that the European bison is a native species. To VFD the primary argument against reintroduction was if it would be at expense of the state. To JS it was if European bison would pose a threat in traffic. Those in VFD representing the nature conservatory stake held the most positive attitudes towards a reintroduction project. Those representing stakes with ties to consumptive land use held the least positive attitudes.